Sampung magkakaibigan - Canon, Kristine; De Jesus, Ruben (Quezon City Adarna House, 2008)
A story about a boy who almost lost his friends
Text in Filipino and English.
Rekomendado sa mga batang edad 6 pataas.
"A book in 2 languages."--Cover.